Strategies for Improving the Safety of Lithium-Ion Batteries in Electric Vehicles - Kastu, Mariel (My University, 2026)
Electric vehicles are becoming increasingly more common because of the fight against climate change. Lithium-ion batteries are the most widely used battery type in electric vehicles due to their superior properties, e.g. high energy and power densities. However, lithium-ion batteries are prone to an exothermic reaction inside the battery called thermal runaway. Thermal runaway results in the failure of the battery and may propagate through the entire battery pack. This poses safety risks to passengers and those around as the reaction can result in a severe battery fire. This thesis examines methods for mitigating the adverse effects of thermal runaway. Methods developed to prevent thermal runaway include battery management systems (BMS), battery pack cooling technologies, and internal battery technologies such as additives and new material options. Battery fires occur despite preventive technologies, therefore methods for identifying thermal runaway using sensors and effectively extinguishing fires by choosing the right extinguishing agents have also been covered in the thesis.

Ilmastonmuutoksen torjunnan vuoksi sähköajoneuvoista on tulossa yhä yleisempiä. Litiumioniakut ovat yleisimmin käytetty akkutyyppi sähköajoneuvoissa niiden erinomaisien ominaisuuksien kuten korkean energia- ja tehotiheyden ansiosta. Litiumioniakut ovat kuitenkin alttiita akun sisällä tapahtuvalle eksotermiselle reaktiolle, jota kutsutaan lämpökarkaamiseksi. Lämpökarkaaminen johtaa akun vikaantumiseen ja voi levitä koko akustoon. Tämä aiheuttaa turvallisuusriskejä matkustajille ja ympärillä oleville henkilöille, koska reaktio voi aiheuttaa voimakkaan akkupalon. Tässä tutkielmassa tarkastellaan menetelmiä lämpökarkaamisen haittojen vähentämiseksi. Lämpökarkaamisen estämiseksi kehitettyjä menetelmiä ovat esimerkiksi akunhallintajärjestelmät (BMS), akuston jäähdytystekniikat sekä akun sisäiset tekniikat kuten lisäaineet ja uudet materiaalivaihtoehdot. Akkupaloja esiintyy ennalta ehkäisevistä teknologioista huolimatta, joten tutkielmassa on käsitelty myös lämpökarkaamisen tunnistamista sensoreiden avulla ja tulipalojen tehokasta sammuttamista esimerkiksi valitsemalla oikeat sammutusaineet.
Keywords: lithium-ion batteries; electric vehicles; fire safety; thermal runaway; litiumioniakut; sähköajoneuvot; paloturvallisuus; lämpökarkaaminen